A solid electrolyte membrane and its preparation method and application
The combination of the ultra-thin PAN thin film frame prepared by liquid phase separation technology and oxide inorganic solid electrolytes solves the problems of low ionic conductivity and poor flexibility of existing solid lithium battery electrolyte materials, and realizes a solid electrolyte membrane with high energy density and long cycle life.
Patent Information
- Application Number
- CN202410115984.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-26
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-01-26
AI Technical Summary
The solid electrolyte materials of existing solid-state lithium batteries have problems such as low ionic conductivity, poor flexibility, fragility and poor contact with the electrode interface, which limits their application and development.
Liquid phase separation technology is used to prepare a high porosity and ultra-thin polyacrylonitrile (PAN) film frame, mix the oxide inorganic solid electrolyte, binder and lithium salt into an electrolyte slurry, fill it in the pores of the film frame, and dry and hot press to form a solid electrolyte membrane.
It realizes high ion transport performance of solid electrolyte membrane, improves the energy density and cycle life of lithium-ion batteries, and is easy to produce on a large scale.
Smart Images

Figure CN117895089B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of solid-state battery technology, and in particular to a solid-state electrolyte membrane and a preparation method and application thereof. Background Art
[0002] The reserves of fossil energy are gradually depleting, and the use of fossil fuels has brought about serious environmental pollution problems and greenhouse effects. New energy represented by wind energy and solar energy is expected to alleviate the current situation of energy shortage, and can also significantly reduce air pollution and greenhouse gas emissions. However, the randomness, volatility and discontinuity of these new energy sources have greatly limited the application of new energy in actual industry. Therefore, it is necessary to develop energy storage devices to store wind energy and solar energy, so energy storage devices play a very important role in new energy systems. Lithium-ion batteries, as a more commonly used energy storage device, have the advantages of high energy density, easy to carry, and many application scenarios. At present, the electrolytes of lithium-ion batteries widely used in electronic products and power batteries are mainly organic flammable electrolytes. The toxicity and flammability of organic flammable electrolytes seriously affect the safety of actual use. The leakage of electrolytes can easily lead to environmental pollution and explosion and fire accidents. In addition, the theoretical energy density of lithium-ion batteries using electrolytes cannot meet the use scenarios with higher requirements. Therefore, researchers have conducted a lot of research on safer solid-state lithium batteries with higher theoretical energy density. Among them, one of the most important components of solid-state lithium batteries is solid electrolytes. At present, solid electrolytes are mainly divided into pure polymer solid electrolytes, inorganic ceramic solid electrolytes and composite solid electrolytes. Among them, inorganic ceramic solid electrolytes are mainly divided into three systems: oxides, sulfides and halides. Among these materials, pure polymer solid electrolytes have good flexibility, but low ionic conductivity (~10 -6 S / cm), although inorganic ceramic solid electrolytes have good ionic conductivity (~10 -3 S / cm), but its problems such as difficulty in thinning, poor flexibility, fragility and poor contact with the electrode interface have become the main reasons limiting its application and development. In addition, the solid electrolyte of the sulfide system easily reacts with water and carbon dioxide in the air, and the solid electrolyte of the halide system has poor compatibility with the electrode, which is not conducive to large-scale application. One of the representative materials of oxide ceramic materials is garnet-type LLZTO, which has high ionic conductivity, wide electrochemical window and relatively stable matching with the lithium metal interface, so it is often used in the field of solid electrolytes, but its mechanical properties still need to be further improved.
[0003] To address the above problems, the researchers developed a composite solid electrolyte that combines polymer and ceramic solid electrolytes, which not only retains high ionic conductivity (10 -4S / cm), and it has the advantages of polymer flexibility and good interface contact. Its preparation routes are mainly divided into two categories: mold casting method: the composite solid electrolyte slurry is dried according to certain specifications through a casting mold, and then cut for use; coating casting method: the composite solid electrolyte slurry is coated on the positive and negative electrodes, and then dried and used directly. Under normal circumstances, the solid electrolyte can only play a good ion transmission performance when the thickness is 5 to 30μm. However, due to the limitations of mold processing, the materials obtained by the mold casting method will result in a larger solid electrolyte thickness of more than 100μm, which greatly reduces the battery energy density; although the coating casting method can reduce the thickness of the solid electrolyte, it will increase the stress between the electrolyte material and the electrode interface during drying, resulting in an increased possibility of side reactions at the interface, making it still face certain challenges to improve the cycle performance. Summary of the invention
[0004] The present application provides a solid electrolyte membrane and a preparation method and application thereof, which can take into account the performances such as ion transport, energy density and cycle life.
[0005] In a first aspect, an embodiment of the present application provides a method for preparing a solid electrolyte membrane, the method comprising:
[0006] Mixing polyacrylonitrile and a water-soluble polymer in a first solvent to obtain a mixed solution;
[0007] The mixed solution is coated to form a film to obtain an intermediate film;
[0008] The intermediate film is immersed in water to remove the water-soluble polymer in the intermediate film, thereby obtaining a film frame with interconnected pores;
[0009] Mixing an oxide inorganic solid electrolyte, a binder and a lithium salt in a second solvent to obtain an electrolyte slurry;
[0010] The electrolyte slurry is filled into the pores of the film frame, and then dried and hot-pressed to convert the electrolyte slurry into an electrolyte composition to obtain a solid electrolyte membrane.
[0011] In the technical scheme of the embodiment of the present application, the film frame is prepared by utilizing liquid phase separation technology, the preparation process is simple, not affected by the fluctuation of environmental humidity and temperature, easy to scale production, and can better control the thickness, porosity, pore size and other properties of the film frame, so as to fill the electrolyte slurry. Secondly, the high porosity and ultra-thin PAN film prepared by liquid phase separation technology is used for the composite solid electrolyte frame, which provides a flexible buffer area for the ceramic electrolyte and gives the composite solid electrolyte good anti-bending ability. The ceramic and polymer electrolyte filled inside it constitute a developed ion transmission network, which can better promote lithium ion transmission. At the same time, hot pressing of the solid electrolyte can further significantly reduce the thickness of the electrolyte film, and the ultra-thin thickness can reduce the ion transmission distance and reduce the quality of the inactive material, thereby helping to improve the rate performance and energy density of the lithium battery; finally, the nitrile group (C≡N) in the PAN polymer chain is a strong electron-withdrawing group with high electrochemical stability. The oxide inorganic solid electrolyte in the electrolyte slurry and the PAN film will undergo dehydrogenation cyanation reaction at the contact interface, enhancing the interface interaction, which will help promote the rapid and continuous Li between the oxide inorganic solid electrolyte and the polymer. + The establishment of a migration path is conducive to the establishment of a stable lithium ion transmission channel. Appropriately reducing the ionic conductivity through PAN can increase the resistance of electron migration between lithium metal and oxide inorganic solid electrolyte, thereby inhibiting the formation of lithium dendrites, thereby improving the rate performance and cycle life of lithium-ion batteries.
[0012] As an optional embodiment, the mass concentration of polyacrylonitrile in the mixed solution is 5% to 15%; and / or
[0013] The mass concentration of the water-soluble polymer in the mixed solution is 5% to 10%; and / or
[0014] The first solvent includes N,N-dimethylformamide.
[0015] In the above implementation process, the greater the mass concentration of polyacrylonitrile and the water-soluble polymer, the greater the viscosity of the mixed solution, which is more conducive to the preparation of the intermediate film; and the smaller the mass concentration of polyacrylonitrile and the water-soluble polymer, the more conducive to the mechanical properties of the film frame. By controlling the mass concentration of polyacrylonitrile in the mixed solution to 5% to 15% and the mass concentration of the water-soluble polymer to 5% to 10%, the difficulty of film frame preparation and mechanical properties can be taken into account.
[0016] As an optional embodiment, the water-soluble polymer includes at least one of polyvinyl pyrrolidone, polyacrylamide, polyacrylic acid, polyvinyl alcohol and polyethylene oxide.
[0017] As an optional embodiment, the coating thickness of the coating film is 100 to 300 μm; and / or
[0018] The thickness of the intermediate film is 10 to 30 μm; and / or
[0019] The film frame has a thickness of 10 to 30 μm; and / or
[0020] The porosity of the film frame is 25% to 60%.
[0021] In the above implementation process, by controlling the thickness of the intermediate membrane and the film frame to 10-30 μm, it is beneficial to obtain a thinner solid electrolyte membrane. By controlling the porosity of the film frame to 25-60%, the mechanical properties of the film frame and the filling amount of the electrolyte composition can be taken into account.
[0022] As an optional embodiment, the soaking temperature is 65-75° C.; and / or
[0023] The soaking time is 8 to 12 hours.
[0024] As an optional embodiment, the mass ratio of the oxide inorganic solid electrolyte, the binder and the lithium salt is 1: (0.5-2): (0.1-2); and / or
[0025] The oxide inorganic solid electrolyte comprises at least one of lithium lanthanum zirconium tantalum oxide and lithium aluminum titanium phosphate; and / or
[0026] The particle size of the oxide inorganic solid electrolyte is not greater than 10 μm; and / or
[0027] The binder comprises at least one of polyvinylidene fluoride, polyethylene oxide, styrene-butadiene rubber and polyacrylic acid; and / or
[0028] The lithium salt includes at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalato)borate and lithium difluorooxalatoborate; and / or
[0029] The second solvent includes at least one of N-methylpyrrolidone, ethanol, acetonitrile, ethylene dichloride, chloroform, acetone, polyethylene glycol, and isopropyl alcohol.
[0030] In the above implementation process, the higher the proportion of binder, the more conducive it is to the bonding strength between the electrolyte composition and the film frame, and the lower the proportion of binder, the more conducive it is to the ionic conductivity of the solid electrolyte membrane. The higher the proportion of lithium salt, the more conducive it is to reducing the resistance of the solid electrolyte membrane, and the lower the proportion of lithium salt, the lower the probability of lithium dendrites, thereby increasing the cycle life of the battery. By controlling the mass ratio of oxide inorganic solid electrolyte, binder and lithium salt to 1: (0.5~2): (0.1~2), the performance of ion transport, energy density and cycle life can be taken into account. The smaller the particle size of the oxide inorganic solid electrolyte, the more conducive it is to filling in the pores of the film frame; controlling the particle size of the oxide inorganic solid electrolyte to be no more than 10μm effectively reduces the difficulty of filling the oxide inorganic solid electrolyte into the pores.
[0031] As an optional embodiment, the electrolyte slurry is filled into the pores of the film frame, and then dried and hot-pressed to convert the electrolyte slurry into an electrolyte composition to obtain a solid electrolyte membrane comprising:
[0032] applying electrolyte slurry to the surface of the film frame;
[0033] The membrane frame coated with the electrolyte slurry is subjected to suction filtration so that the electrolyte slurry fills the pores of the membrane frame;
[0034] Drying and hot pressing the film frame filled with the electrolyte slurry to convert the electrolyte slurry into an electrolyte composition to obtain a solid electrolyte membrane;
[0035] Among them, the filtration time is 30 to 180 seconds, and the vacuum pump pressure of the filtration is 80 to 90 kPa.
[0036] As an optional embodiment, the mass of the electrolyte composition is 50% to 60% of the total mass of the solid electrolyte membrane; and / or
[0037] The thickness of the solid electrolyte membrane is 10 to 30 μm.
[0038] In the above implementation process, the greater the mass proportion of the electrolyte composition, the more beneficial it is to the lithium ion transmission performance of the solid electrolyte membrane, and the smaller the mass proportion of the electrolyte composition, the more beneficial it is to the mechanical properties of the solid electrolyte membrane. By controlling the mass proportion of the electrolyte composition, the mechanical properties and lithium ion transmission performance of the solid electrolyte membrane can be balanced. The thicker the thickness of the solid electrolyte membrane, the more beneficial it is to the mechanical properties of the solid electrolyte membrane. The thinner the thickness of the solid electrolyte membrane, the more beneficial it is to the control of the mass of inactive substances in the solid electrolyte membrane, and thus to the energy density of the battery. By controlling the thickness of the solid electrolyte membrane to 10 to 30 μm, the mechanical properties of the solid electrolyte membrane and the energy density of the battery can be taken into account.
[0039] In a second aspect, an embodiment of the present application further provides a solid electrolyte membrane, which is prepared by the method provided in the first aspect.
[0040] In a third aspect, an embodiment of the present application further provides a solid-state lithium battery, the solid-state lithium battery comprising the solid-state electrolyte membrane provided in the second aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0042] Figure 1 is a flow chart of the method provided in the embodiment of the present application;
[0043] Figure 2 is a low-magnification SEM photograph of a PAN film frame plane obtained from a DMF solution containing 7.5 wt % PAN and 15 wt % PVP in Example 1 of the present invention;
[0044] Figure 3 This is a high-magnification SEM photograph of a PAN film frame plane obtained from a DMF solution containing 7.5 wt % PAN and 15 wt % PVP in Example 1 of the present invention;
[0045] Figure 4 is a SEM photograph of a cross section of a PAN film frame obtained from a DMF solution of 7.5 wt % PAN and 15 wt % PVP in Example 1 of the present invention;
[0046] Figure 5 is a low-magnification SEM photograph of a PAN film frame plane obtained from a DMF solution containing 10 wt % PAN and 6.67 wt % PVP in Example 2 of the present invention;
[0047] Figure 6 This is a high-magnification SEM photograph of a PAN film frame plane obtained from a DMF solution containing 10 wt % PAN and 6.67 wt % PVP in Example 2 of the present invention;
[0048] Figure 7 is a SEM photograph of a cross section of a PAN film frame obtained from a DMF solution of 10 wt % PAN and 6.67 wt % PVP in Example 2 of the present invention;
[0049] Figure 8is a low-magnification SEM photograph of a PAN film frame plane obtained from a DMF solution of 6.67 wt % PAN and 10 wt % PVP in Example 3 of the present invention;
[0050] Fig. 9 This is a high-magnification SEM photograph of a PAN film frame plane obtained from a DMF solution containing 6.67 wt % PAN and 10 wt % PVP in Example 3 of the present invention;
[0051] Fig.10 is a SEM photograph of a cross section of a PAN film frame obtained from a DMF solution of 6.67 wt % PAN and 10 wt % PVP in Example 3 of the present invention;
[0052] Fig.11 This is a SEM photo of LLZTO powder obtained by sieving in Example 4 of the present invention;
[0053] Fig.12 This is the XRD pattern of LLZTO powder purchased in Example 4 of the present invention;
[0054] Fig.13 This is a low-magnification SEM photograph of the solid electrolyte membrane obtained in Example 5 of the present invention when the mass ratio of LLZTO, PEO, and LiTFSI is 8:8:1.
[0055] Fig.14 This is a planar high-magnification SEM photograph of the solid electrolyte membrane obtained in Example 5 of the present invention when the mass ratio of LLZTO, PEO, and LiTFSI is 8:8:1.
[0056] Fig.15 This is a cross-sectional SEM photograph of the solid electrolyte membrane obtained in Example 5 of the present invention when the mass ratio of LLZTO, PEO, and LiTFSI is 8:8:1.
[0057] Fig.16 Example 5 of the present invention at 0.1 mA / cm 2 The following is a lithium symmetric battery cycle curve using the solid electrolyte membrane of the present invention.
[0058] Fig.17 In Example 5 of the present invention, the 2 Next, at 0.2 mA / cm 2 The following is a lithium symmetric battery cycle curve using the solid electrolyte membrane of the present invention. DETAILED DESCRIPTION
[0059] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0060] The solid electrolyte membrane prepared by the current method is usually more than 100μm thick, or there is a large stress between the electrode, resulting in poor performance such as ion transport, energy density and cycle life. For this reason, the inventors tried to use electrospinning to prepare a PAN film frame and fill the electrolyte slurry into the pores of the film frame to reduce the thickness of the entire solid electrolyte membrane. However, electrospinning has high requirements for production equipment and is easily affected by environmental conditions such as temperature and humidity. It has certain limitations in large-scale production.
[0061] The present application intends to provide a solid electrolyte membrane and a preparation method and application thereof, so as to obtain a solid electrolyte membrane that can take into account the performance of ion transport, energy density and cycle life while being easy to mass produce.
[0062] Figure 1 is a flow chart of the method provided in the embodiment of the present application, such as Figure 1 As shown, the embodiment of the present application provides a method for preparing a solid electrolyte membrane, the method comprising:
[0063] S1. mixing polyacrylonitrile and a water-soluble polymer in a first solvent to obtain a mixed solution;
[0064] In some embodiments, the mass concentration of polyacrylonitrile in the mixed solution is 5% to 15%; the mass concentration of the water-soluble polymer in the mixed solution is 5% to 10%; and the first solvent includes N,N-dimethylformamide. The greater the mass concentration of polyacrylonitrile and the water-soluble polymer, the greater the viscosity of the mixed solution, which is more conducive to the preparation of the intermediate film; and the smaller the mass concentration of polyacrylonitrile and the water-soluble polymer, the more conducive to the mechanical properties of the film frame. By controlling the mass concentration of polyacrylonitrile in the mixed solution to 5% to 15% and the mass concentration of the water-soluble polymer to 5% to 10%, the difficulty of preparing the film frame and the mechanical properties can be taken into account. By adjusting the mass fraction ratio of PAN and the water-soluble polymer, the porosity of the final film frame is controlled to be 25 to 60%. Excessive porosity will reduce the mechanical properties of the film frame, and too small porosity will lead to insufficient filling of the electrolyte slurry, resulting in a decrease in the ionic conductivity of the composite solid electrolyte membrane.
[0065] In some embodiments, the water-soluble polymer includes at least one of polyvinyl pyrrolidone (PVP), polyacrylamide (PAM), polyacrylic acid (PAA), polyvinyl alcohol (PVA), and polyethylene oxide (PEO).
[0066] S2. The mixed solution is coated to form a film to obtain an intermediate film;
[0067] In some embodiments, the coating thickness of the coating film is 100-300 μm; the thickness of the intermediate film is 10-30 μm; the thickness of the film frame is 10-30 μm; and the porosity of the film frame is 25%-60%. By controlling the thickness of the intermediate film and the film frame to be 10-30 μm, it is beneficial to prepare a thinner solid electrolyte membrane, and by controlling the porosity of the film frame to be 25-60%, it is possible to take into account both the mechanical properties of the film frame and the filling amount of the electrolyte composition.
[0068] The specific process of coating and film formation can be: the solution is uniformly scraped onto the surface of a clean glass plate by a coater, and the organic solvent is dried in an oven to obtain an intermediate film.
[0069] S3. Soaking the intermediate membrane in water to remove the water-soluble polymer in the intermediate membrane, thereby obtaining a thin film frame with interconnected pores.
[0070] In some embodiments, the soaking temperature is 65-75° C. and the soaking time is 8-12 hours.
[0071] S4. The oxide inorganic solid electrolyte, the binder and the lithium salt are mixed in a second solvent to obtain an electrolyte slurry;
[0072] In some embodiments, the mass ratio of the oxide inorganic solid electrolyte, the binder and the lithium salt is 1: (0.5-2): (0.1-2); the oxide inorganic solid electrolyte includes at least one of lithium lanthanum zirconium tantalum oxide and lithium aluminum titanium phosphate; the particle size of the oxide inorganic solid electrolyte is not greater than 10 μm; the binder includes at least one of polyvinylidene fluoride, polyethylene oxide, styrene-butadiene rubber and polyacrylic acid; the lithium salt includes at least one of bistrifluoromethanesulfonyl imide lithium, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalate)borate and lithium difluorooxalateborate; the second solvent includes at least one of N-methylpyrrolidone, ethanol, acetonitrile, dichloroethane, chloroform, acetone, polyethylene glycol and isopropanol. The higher the proportion of the binder, the more favorable it is for the bonding strength between the electrolyte composition and the film frame, and the lower the proportion of the binder, the more favorable it is for the ionic conductivity of the solid electrolyte membrane. The higher the proportion of the lithium salt, the more favorable it is for the resistance of the solid electrolyte membrane to be reduced, and the lower the proportion of the lithium salt, the more it can reduce the probability of lithium dendrites, thereby increasing the cycle life of the battery. By controlling the mass ratio of oxide inorganic solid electrolyte, binder and lithium salt to 1: (0.5-2): (0.1-2), the performance of ion transport, energy density and cycle life can be taken into account. The smaller the particle size of the oxide inorganic solid electrolyte, the more conducive it is to fill in the pores of the film frame; controlling the particle size of the oxide inorganic solid electrolyte to no more than 10μm effectively reduces the difficulty of filling the oxide inorganic solid electrolyte into the pores.
[0073] Among them, the oxide inorganic solid electrolyte can be obtained by purchasing or preparing from the market. The preparation of LLZTO is illustrated below as an example: lithium carbonate, lanthanum oxide, zirconium oxide, and tantalum oxide in a certain stoichiometric ratio are used as raw materials for synthesizing LLZTO, wherein lithium carbonate is excessively added, the raw materials are added to a planetary ball mill and ball milled at a certain speed, and then heated to a certain temperature in a muffle furnace to allow the raw materials to fully react, and then high-speed ball milling is performed under argon protection, and sieved to prepare LLZTO with controllable particle size, wherein the ratio of lithium carbonate, lanthanum oxide, zirconium oxide, and tantalum oxide can be (6-7.5): (2-3): (1-2): (0.3-0.7). During the high-temperature sintering process, the lithium element is easily volatilized, so lithium carbonate is additionally added at a rated ratio of 10wt% to 30wt%. The ball milling speed is 200-600rpm, and the ball milling time is 6-36 hours. Usually, during the ball milling process, if the speed is too low, a longer ball milling time will be required. If the speed is too high, a large amount of heat will be generated in a short time, which has certain safety hazards. In addition, if the ball milling time is too short, the ball milling will be insufficient, and if the time is too long, the service life of the instrument will be affected. The reaction temperature is 750-1200℃, where the heating and cooling rates are 3℃ / min, and the insulation time is 12-18 hours. In the process of high-temperature solid-phase synthesis of LLZTO, if the reaction temperature is too high or too low, other side reactions will occur, affecting the cubic LLZTO structure. If the heating and cooling rate is too high, the sample will be heated unevenly. If the heating and cooling rate is too low, the side reactions will increase. If the insulation time is too short, the reaction will be insufficient. If the insulation time is too long, the lithium element will be lost too much. The size of the prepared LLZTO is below 10μm, which is conducive to its filling into the pores of the frame film.
[0074] S5. Filling the electrolyte slurry into the pores of the film frame, and then drying and hot pressing to convert the electrolyte slurry into an electrolyte composition to obtain a solid electrolyte membrane.
[0075] In some embodiments, the electrolyte slurry is filled into the pores of the film frame, and then dried and hot-pressed to obtain a solid electrolyte membrane comprising:
[0076] S5.1. Applying electrolyte slurry to the surface of the film frame;
[0077] S5.2. Filter the film frame coated with the electrolyte slurry to fill the electrolyte slurry in the pores of the film frame; wherein, the filtration time is 30 to 180 seconds, the vacuum pump pressure of the filtration is 80 to 90 kPa, and the filtration is carried out in an argon atmosphere.
[0078] S5.3. The film frame filled with the electrolyte slurry is dried and hot-pressed to convert the electrolyte slurry into an electrolyte composition to obtain a solid electrolyte membrane;
[0079] This method uses liquid phase separation technology to prepare a film frame. The preparation process is simple, not affected by fluctuations in environmental humidity and temperature, easy to scale up, and can better control the thickness, porosity, pore size and other properties of the film frame for the filling of electrolyte slurry. Secondly, the high-porosity and ultra-thin PAN film prepared by liquid phase separation technology is used for the composite solid electrolyte frame, providing a flexible buffer area for the ceramic electrolyte and giving the composite solid electrolyte good anti-bending ability. The ceramic and polymer electrolyte filled inside it constitute a developed ion transmission network, which can better promote lithium ion transmission. At the same time, hot pressing of the solid electrolyte can further significantly reduce the thickness of the electrolyte film. The ultra-thin thickness can reduce the ion transmission distance and reduce the mass of inactive materials, thereby improving the rate performance and energy density of lithium batteries. Finally, the nitrile group (C≡N) in the PAN polymer chain is a strong electron-withdrawing group with high electrochemical stability. The oxide inorganic solid electrolyte in the electrolyte slurry and the PAN film will undergo a dehydrogenation cyanation reaction at the contact interface, enhancing the interface interaction, which will help promote the rapid and continuous Li-ion transfer between the oxide inorganic solid electrolyte and the polymer. + The establishment of a migration path is conducive to the establishment of a stable lithium ion transmission channel. Appropriately reducing the ionic conductivity through PAN can increase the resistance of electron migration between lithium metal and oxide inorganic solid electrolyte, thereby inhibiting the formation of lithium dendrites, thereby improving the rate performance and cycle life of lithium-ion batteries.
[0080] An embodiment of the present application provides a solid electrolyte membrane, which is prepared by the method provided by the first aspect.
[0081] The solid electrolyte membrane system is prepared based on the above method. The specific steps of the method can refer to the above embodiment. Since the solid electrolyte membrane adopts part or all of the technical solutions of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment, which will not be repeated here.
[0082] The embodiment of the present application provides a solid-state lithium battery, which includes the solid-state electrolyte membrane provided above. Specifically, lithium metal is used as the negative electrode, lithium iron phosphate is used as the positive electrode, and the solid-state electrolyte membrane is assembled to form a battery.
[0083] The solid electrolyte membrane of the present application is further described in detail below in conjunction with the embodiments.
[0084] Example 1
[0085] This example shows the use of a DMF solution with a mass fraction of 7.5 wt% PAN and 15 wt% PVP to prepare a PAN film frame. The specific preparation process is as follows:
[0086] 2 g of PAN, 4 g of PVP and DMF were used to prepare 26.7 g of liquid phase separation precursor liquid, and a porous PAN film frame was prepared under the conditions of a coating thickness of 100 μm and a drying temperature of 60° C.
[0087] Figure 2 This is a low-magnification SEM image of the PAN film frame plane prepared using a DMF solution with a mass fraction of 7.5wt% PAN and 15wt% PVP. Figure 2 It can be seen that the pore structure of the porous PAN film framework prepared by the liquid phase separation method has been formed, with a large number of pore structures.
[0088] Figure 3 This is a high-magnification SEM photo of the PAN film frame plane prepared using a DMF solution with a mass fraction of 7.5wt% PAN and 15wt% PVP. Figure 3 It can be seen that the pore structure of the porous PAN film framework layer prepared by the liquid phase separation method is not continuous, and there are a large number of structural discontinuity areas that affect its mechanical strength.
[0089] Figure 4 Figure 2 is a SEM image of a cross section of a PAN film frame prepared using a DMF solution of 7.5 wt% PAN and 15 wt% PVP. Figure 4 It can be seen that the thickness of the porous PAN film framework prepared by the liquid phase separation method is about 50 μm.
[0090] Example 2
[0091] This example shows the use of a DMF solution with a mass fraction of 10 wt% PAN and 6.67 wt% PVP to prepare a PAN film frame. The specific preparation process is as follows:
[0092] 30 g of liquid phase separation precursor liquid was prepared using 3 g of PAN, 2 g of PVP and DMF, and a PAN film frame was prepared under the conditions of a coating thickness of 100 μm and a drying temperature of 60° C.
[0093] Figure 5 This is a low-magnification SEM image of the PAN film frame plane prepared using a DMF solution with a mass fraction of 10 wt% PAN and 6.67 wt% PVP. Figure 5 It can be seen that the pore structure of the porous PAN film framework obtained by the liquid phase separation method has been formed, and it is a regular circular hole, but the density of the pore structure is not high, which is not conducive to the infusion of materials such as LLZTO, and thus is not conducive to the conduction of lithium ions.
[0094] Figure 6This is a high-magnification SEM photo of the PAN film frame plane prepared using a DMF solution with a mass fraction of 10wt% PAN and 6.67wt% PVP. Figure 6 It can be seen that the pore size of the porous PAN film framework prepared by the liquid phase separation method is small.
[0095] Figure 7 Figure 2 is a SEM image of a cross section of a PAN film frame prepared using a DMF solution of 10 wt% PAN and 6.67 wt% PVP. Figure 7 It can be seen that the thickness of the porous PAN film framework prepared by the liquid phase separation method is about 12 μm.
[0096] Example 3
[0097] This example shows the use of a DMF solution with a mass fraction of 6.67wt% PAN and 10wt% PVP to prepare a PAN film frame. The specific preparation process is as follows:
[0098] 2 g of PAN, 3 g of PVP and DMF were used to prepare 30 g of liquid phase separation precursor liquid, and a PAN film frame was prepared under the conditions of a coating thickness of 100 μm and a drying temperature of 60° C.
[0099] Figure 8 This is a low-magnification SEM image of the PAN film frame plane prepared using a DMF solution with a mass fraction of 6.67wt% PAN and 10wt% PVP. Figure 8 It can be seen that the pore structure of the porous PAN film framework prepared by the liquid phase separation method has been formed, has more pores, and can maintain the basic mechanical structure of the PAN framework.
[0100] Fig. 9 This is a high-magnification SEM photo of the PAN film frame plane prepared using a DMF solution with a mass fraction of 6.67wt% PAN and 10wt% PVP. Fig. 9 It can be seen that the porous PAN film framework prepared by the liquid phase separation method has a more appropriate pore structure size and transparent pores, which is conducive to the infusion of materials such as LLZTO, thereby facilitating the conduction of lithium ions.
[0101] Fig.10 The following is a SEM image of a cross section of a PAN film frame prepared using a DMF solution containing 6.67 wt% PAN and 10 wt% PVP. Fig.10 It can be seen that the thickness of the porous PAN film frame prepared by the liquid phase separation method is about 12 μm, which meets the use requirements of ultra-thin composite solid electrolytes.
[0102] Example 4
[0103] This example shows the treatment of purchased LLZTO garnet solid electrolyte powder, and the specific treatment process is as follows:
[0104] The LLZTO garnet solid electrolyte powder was sieved in sequence using 50, 500, 1000, and 2000 mesh sieves.
[0105] Fig.11 This is a SEM photo of LLZTO powder obtained by sieving. Fig.11 It can be seen that the particle size of the LLZTO powder obtained by sieving is 0.1-10μm, which can be well adapted to the PAN ultra-thin film frame.
[0106] Fig.12 This is the XRD pattern of the purchased LLZTO powder. Fig.12 It can be seen that the purchased LLZTO powder has the characteristic diffraction peak of garnet-type crystals, indicating that the purchased LLZTO has a garnet-type crystal structure.
[0107] Example 5
[0108] Preparation of solid electrolyte membrane, the specific preparation process is as follows:
[0109] The film frame of Example 3 and the LLZTO of Example 4 were selected, and 2 g, 2 g, and 0.25 g of LLZTO, PEO, and LiTFSI were added to 20 g of acetonitrile in an argon atmosphere, and magnetic stirring was performed for 8 h at 60 ° C to obtain an electrolyte slurry. The obtained electrolyte slurry was evenly coated on the PAN film, and after being allowed to stand for 30 seconds, it was filtered for 30 seconds using a sand core filtration device, wherein the vacuum pump pressure was 80-90 kPa. The composite solid electrolyte was removed and placed in a vacuum oven at 60 ° C for vacuum drying to obtain a solid electrolyte membrane.
[0110] Fig.13 This is a low-magnification SEM photo of the solid electrolyte membrane obtained. Fig.13 It can be seen that the electrolyte slurry has completely filled the pores of the PAN film framework, the electrolyte is evenly distributed, and the surface is flat, which can provide good interface contact.
[0111] Fig.14 This is a high-magnification SEM photo of the solid electrolyte membrane obtained. Fig.14 It can be seen that there is a complete connection pathway between the LLZTO garnet crystals, which can better complete the transmission of lithium ions.
[0112] Fig.15 is a cross-sectional SEM photograph of the obtained solid electrolyte membrane. Fig.15It can be seen that the thickness of the composite solid electrolyte is about 15 μm, which meets the ultra-thin standard.
[0113] CR2032 battery shells were used for battery assembly, where the lithium metal sheet on one side had a diameter of 16 mm and the lithium metal sheet on the other side had a diameter of 12 mm, both with a thickness of 0.2 mm, and the solid electrolyte membrane prepared in the above steps. The electrochemical performance test was completed on a NEWARE battery test system with a test current of 0.1 and 0.2 mA / cm 2 .
[0114] Fig.16 is 0.1mA / cm 2 The following is the cycle curve of a lithium symmetric battery using this solid electrolyte membrane. Fig.16 It can be seen that this solid electrolyte membrane has a 2 The ability to perform lithium symmetric battery cycling under low temperatures and the overpotential does not increase but decreases during the 90-hour long cycle process, indicating its good cycle stability.
[0115] Fig.17 First, at 0.1 mA / cm 2 Next, at 0.2 mA / cm 2 The following is the cycle curve of lithium symmetric battery using this solid electrolyte membrane. Fig.17 It can be seen that this solid electrolyte membrane has a 2 The ability to cycle lithium symmetric batteries at 0.1 mA / cm 2 To 0.2mA / cm 2 When the current density changes, the overpotential increases to a lower degree, indicating that this solid electrolyte membrane has good lithium ion transport capability.
[0116] Example 6
[0117] Except for using the film frame provided in Example 1, the rest of the contents of this embodiment are the same as those of Example 5.
[0118] Example 7
[0119] Except for using the film frame provided in Example 2, the rest of the contents of this embodiment are the same as those of Example 5.
[0120] The above are only specific embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing a solid electrolyte membrane, characterized in that: The method comprises: Mixing polyacrylonitrile and a water-soluble polymer in a first solvent to obtain a mixed solution; The mixed solution is coated to form a film to obtain an intermediate film; Soaking the intermediate film in water to remove water-soluble polymers in the intermediate film, thereby obtaining a film frame with interconnected pores; Mixing an oxide inorganic solid electrolyte, a binder and a lithium salt in a second solvent to obtain an electrolyte slurry; Filling the electrolyte slurry into the pores of the film frame, and then drying and hot pressing to convert the electrolyte slurry into an electrolyte composition to obtain a solid electrolyte membrane; Wherein, the mass concentration of polyacrylonitrile in the mixed solution is 6.67%, and the mass concentration of the water-soluble polymer in the mixed solution is 10%; The electrolyte slurry is filled into the pores of the film frame, and then dried and hot-pressed to convert the electrolyte slurry into an electrolyte composition to obtain a solid electrolyte membrane, which includes: coating the electrolyte slurry on the surface of the film frame; filtering the film frame coated with the electrolyte slurry to fill the electrolyte slurry in the pores of the film frame; drying and hot-pressing the film frame filled with the electrolyte slurry to convert the electrolyte slurry into an electrolyte composition to obtain a solid electrolyte membrane; wherein the filtration time is 30 to 180 seconds, and the vacuum pump pressure of the filtration is 80 to 90 kPa.
2. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The first solvent includes N,N-dimethylformamide.
3. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The water-soluble polymer includes at least one of polyvinyl pyrrolidone, polyacrylamide, polyacrylic acid, polyvinyl alcohol and polyethylene oxide.
4. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The coating thickness of the coating film is 100 to 300 μm; and / or The thickness of the intermediate film is 10 to 30 μm; and / or The film frame has a thickness of 10 to 30 μm; and / or The porosity of the film frame is 25% to 60%.
5. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The soaking temperature is 65-75°C; and / or The soaking time is 8 to 12 hours.
6. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The mass ratio of the oxide inorganic solid electrolyte, the binder and the lithium salt is 1:(0.5-2):(0.1-2); and / or The oxide inorganic solid electrolyte comprises at least one of lithium lanthanum zirconium tantalum oxide and lithium aluminum titanium phosphate; and / or The particle size of the oxide inorganic solid electrolyte is not greater than 10 μm; and / or The binder comprises at least one of polyvinylidene fluoride, polyethylene oxide, styrene-butadiene rubber and polyacrylic acid; and / or The lithium salt comprises at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalatoborate) and lithium difluorooxalatoborate; and / or The second solvent includes at least one of N-methylpyrrolidone, ethanol, acetonitrile, ethylene dichloride, chloroform, acetone, polyethylene glycol and isopropanol.
7. The method for preparing a solid electrolyte membrane according to claim 1, characterized in that: The mass of the electrolyte composition is 50% to 60% of the total mass of the solid electrolyte membrane; and / or The thickness of the solid electrolyte membrane is 10 to 30 μm.
8. A solid electrolyte membrane, characterized in that: The solid electrolyte membrane is prepared by the method according to any one of claims 1 to 7.
9. A solid-state lithium battery, characterized in that: The solid-state lithium battery comprises the solid-state electrolyte membrane according to claim 8.
Citation Information
Patent Citations
Dual solvent step-by-step phase conversion preparation method of polymethyl methacrylate gel electrolyte microporous membrane
CN107394265A
A composition for preparing a membrane comprisingpolyacrylonitrile, a membrane prepared with the same,and a preparation method thereof
KR1020050117090A